PERILAKU PENGGEREKAN DAN PERKEMBANGBIAKAN KUMBANG AMBROSIA PLATYPUS TREPANATUS PADA DOLOK RAMIN - P Sukartana (Jurnal Penelitian Hasil Hutan, 1987)
The tunneling and breeding habits of ambrosia beetle Platypus trepanatus  Chapman  (Coleoptera: Platypodidae)  were studied  in the field for 26 days after  initial burrowing.The tunneling  is initiated  by the male beetle, commenced  hours after  the ramin tree (Gonystylus  bancanus  Kurz.)  is felled.  As the beetle tunnel about twice its body length,  the burrowing is stopped,  and the beetle, then, remains inside near the entrance hole to entice  the female  beetle for  joining.After arriving, the female  beetle takes over the tunneling extension.  The male, on the other hand, occupies the initial tunnel, builds a circular fibrous  plait  ringed at the entrance hole, and cleans the tunnel  by ejecting frass outside. An established  tunnel  is determined  by  the ejection  of coarse frass  first  and  the fine  other then.  A successful  tunneling  (broods)  seems  to be attributable  to the parent  beetles care.The beetle tends to burrow  the log across the grain.  The first tunneling  is radially, but by the day about  12, it has significantly  curved.  The speed of tunneling  is approximately  4.47 mm  while the depth  of its penetration   is about  2.56  mm per  day.The oviposition  is firstly  recorded between  the day 2-8 at the length of tunnel 9-25 mm. The egg stadium  is about  two weeks.  No pupation was shown  during  these 26 day studies.Statistical  computations   reflect  that the tunneling  and oviposition  were still continued  after  these observations